Wavelength Width Dependence of Cavity Temperature Distribution in Semiconductor Diode Laser. (27th October 2013) - Abbasi, S. P.; Alimorady, A.
Abstract : The study of heat distribution in laser diode shows that there is nonuniform temperature distribution in cavity length of laser diode. In this paper, we investigate the temperature difference in laser diode cavity length and its effect on laser bar output wavelength width that mounted on usual CS model. In this survey at the first, laser was simulated then the simulations result was compared with experimental test result. The result shows that for each emitter there is difference, about 2.5 degree between the beginning and end of cavity.